1995
DOI: 10.1177/088307389501000412
|View full text |Cite
|
Sign up to set email alerts
|

The Determination of Sensory Deficits in Children With Hemiplegic Cerebral Palsy

Abstract: Cerebral paisy is a non-progressive disorder associated with brain in jury, detect, or dlsease, of early onset. Emphasis IS placed on the more easily observable motor deficits, with any underlying sensory deficits often being overlooked. Existing sensory assessments have either been standardized on an adult population or for a paediatric population without significant neuromotor impalrment. Thus, there is a need to formulate a standardized sensory assessment battery that may be used to evaluate physically hand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
151
6
8

Year Published

2001
2001
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(178 citation statements)
references
References 63 publications
(136 reference statements)
13
151
6
8
Order By: Relevance
“…The probability of correctly guessing at least seven of 10 trials is 17% while the probability of correctly guessing five in succession in a series of 10 trials is 11%, providing the distribution is binomial. Stereognosis is the tactile modality most often evaluated and reported to be impaired in children with CP (Uvebrant 1988, Yekutiel et al 1994, Cooper et al 1995. However, in this study all children with deficient stereognosis of familiar objects also failed the 2PD at 7mm.…”
Section: Clinical Implications: Which Assessments Are Useful?contrasting
confidence: 42%
See 1 more Smart Citation
“…The probability of correctly guessing at least seven of 10 trials is 17% while the probability of correctly guessing five in succession in a series of 10 trials is 11%, providing the distribution is binomial. Stereognosis is the tactile modality most often evaluated and reported to be impaired in children with CP (Uvebrant 1988, Yekutiel et al 1994, Cooper et al 1995. However, in this study all children with deficient stereognosis of familiar objects also failed the 2PD at 7mm.…”
Section: Clinical Implications: Which Assessments Are Useful?contrasting
confidence: 42%
“…Children with hemiplegic cerebral palsy (CP) commonly exhibit tactile sensory deficiencies in their hands in addition to motor problems (Mihran and Tachdjian 1958;Wilson and Wilson 1967a, b;Uvebrant 1988;Lesný et al 1993;Cooper et al 1995). Sensory input is essential for fine manual dexterity (Moberg 1962, Callahan 1990, Pehoski 1995, Gordon and Duff 1999, and a lack of sensory input causes delayed learning of new motor tasks (Asanuma and Arissian 1984), clumsiness, lack of precision, and can result in an unused extremity (Taub 1976, Taub andWolf 1997).…”
mentioning
confidence: 99%
“…About 90% of children with CP present with sensory dysfunction such as tactile and proprioceptive deficits (Cooper et al, 1995). The impaired central nervous system in CP produces not only abnormal muscle tone but also sensory disturbances (Cooper et al, 1995).…”
Section: ⅰ Introductionmentioning
confidence: 99%
“…27 Although CP is commonly described as a motor impairment, radiological evidence of structural pathology beyond the motor area is common, and bilateral CNS lesions occur in a significant proportion of children with hemiplegic CP. 28,29 It has also been demonstrated that a significant proportion of children show functional impairment in the non-affected hand 30 and, in comparison with healthy age-matched controls, 31 this is associated with bilateral parenchymal lesions on magnetic resonance imaging. 30 It is possible that the extent of the cerebral pathology in hemiplegia could affect process skill ability.…”
Section: Discussionmentioning
confidence: 99%